2020
DOI: 10.1021/acs.macromol.0c01057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Confinement on Solvent-Driven Infiltration of the Polymer into Nanoparticle Packings

Abstract: Nanocomposite films containing a high volume fraction (>50 vol %) of nanoparticles (NPs) in a polymer matrix are promising for their functionality and use as structural coatings and also provide a unique platform to understand polymer behavior under strong confinement. Previously, we developed a novel technique to fabricate such nanocomposites at room temperature using solvent-driven infiltration of polymer (SIP) into NP packings. In the SIP process, a bilayer made of an underlying polymer film and a dense pac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…, the Flory interaction parameter χ ≈ 0, and the dispersion behavior is solely determined by the conformational entropy of the polymers at the particle–polymer interface. However there is a dearth of studies focusing on highly loaded PNCs with χ ≠ 0, 40,41 which can provide additional tools to control the phase behavior and thus their functional properties as has been demonstrated recently. 44,45…”
Section: Introductionmentioning
confidence: 99%
“…, the Flory interaction parameter χ ≈ 0, and the dispersion behavior is solely determined by the conformational entropy of the polymers at the particle–polymer interface. However there is a dearth of studies focusing on highly loaded PNCs with χ ≠ 0, 40,41 which can provide additional tools to control the phase behavior and thus their functional properties as has been demonstrated recently. 44,45…”
Section: Introductionmentioning
confidence: 99%
“…44 Interestingly, the extent of infiltration was independent of the confinement degree with strongly confined to even more strongly confined polymers achieving a similar extent of infiltration. 44 Thus, one would expect the majority of the changes to polymer dynamics to occur when the degree of confinement is closer to one, indicating similar polymer and pore size. Molecular dynamics (MD) simulations were employed to investigate the polymer infiltration into a disordered nanoparticle assembly while varying polymer–nanoparticle interactions.…”
Section: Introductionmentioning
confidence: 97%
“…Further experimental work investigated polymer infiltration rates into nanoparticle assemblies, and the authors found that the polymer infiltration rate significantly slowed as the degree of confinement increased. 44 Interestingly, the extent of infiltration was independent of the confinement degree with strongly confined to even more strongly confined polymers achieving a similar extent of infiltration. 44 Thus, one would expect the majority of the changes to polymer dynamics to occur when the degree of confinement is closer to one, indicating similar polymer and pore size.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations